The Study of the Analytical Thinking Ability of the Students in Faculty of Education, Suratthani Rajabhat University - อักษรกาญจน์, สุรีรัตน์ (Ratchaphruek Journal, 2019)
This study intended to explore the analytical thinking ability of the students in Faculty of Education, Suratthani Rajabhat University. The sample group of the study were 1,834 students in 2016 academic year. The analytical thinking assessment designed based on Benjamin S. Bloom’s concept of analytical thinking was employed to assess analytical the students ‘thinking ability. The percentage was used in data analysis. The result show that the students reached the minimum level of analytical thinking ability, 58.22%. The researcher further analyzed analytical thinking ability of the sample in different aspects including importance, relation, and principle. It is found that the students reached minimum level in the aspect of importance and the medium level of critical thinking ability in the aspects of principle and relation respectively.